Perlindungan Konsumen dalam Transaksi Syariah: Prespektif Hukum Islam - Rohmatul Jannah; Keisya Oktavia Afida Denna; Theo Galih Prayudha; Deriel Pratama Putra; Riyan Destra Dwi Ardianto; Sheva Andika Ramajagandhi; Essa Hertiana; Ikhwan Nur Ramadhan; Nur Rofiq (Lembaga Pengembangan Kinerja Dosen, 2025)
The urgency of consumer protection in Sharia-compliant transactions has become increasingly prominent alongside the growth of the halal industry and rising public awareness of transactional justice based on Islamic principles. This study aims to formulate the theoretical and normative construction of consumer protection within the framework of Islamic law and to assess its compatibility with Indonesia’s positive legal system. Employing a normative juridical approach combined with a descriptive-analytical method, this research explores primary legal sources including Qur’anic verses, the hadiths of Prophet Muhammad (PBUH), and scholarly opinions found in classical and contemporary fiqh al-mu‘āmalāt literature, as well as secondary legal sources such as Law Number 8 of 1999 on Consumer Protection, fatwas of the National Sharia Council (DSN-MUI), and relevant academic literature. The analysis is conducted through content analysis to extract the values of justice, transparency, and balance of rights and obligations within contractual mechanisms. This study finds that core principles such as truthfulness (ṣidq), disclosure (bayān), and justice (‘adālah) constitute the essential foundation of consumer protection in the Islamic legal perspective. The prohibition of gharar (uncertainty), riba (usury), and tadlīs (fraudulent misrepresentation) is not merely a moral injunction but an integral safeguard mechanism for consumer rights. Furthermore, the institutional presence of supervisory bodies such as DSN-MUI and Sharia certification mechanisms has proven to be strategic, though they continue to face challenges in implementation, socialization, and consumer literacy. The findings also indicate a substantial opportunity for harmonizing Islamic legal principles with the national legal system within the framework of maqāṣid al-sharī‘ah. Therefore, this study recommends strengthening sectoral regulations based on Sharia principles, integrating fatwas into positive legal norms, and enhancing educational capacity for both business actors and consumers in order to realize ethical, equitable, and sustainable transactions.